The Effect of Implementing the STAD Type Cooperative Learning Model Through The Hand-On Mathematics Technique on Students' HOTS Abilities in The Exponent and Logarithm Material in Tenth Grade High School - Erna, Erna; Ramalisa, Yelli; Simatupang, Gugun M (OMEGA: Jurnal Keilmuan Pendidikan Matematika, 2025)
The low level of students’ higher-order thinking skills (HOTS) in solving abstract mathematics problems highlights the need for active and collaborative learning. The Student Teams Achievement Division (STAD) cooperative learning model combined with Hands On Mathematics emphasizes direct student engagement.This study aimed to improve HOTS on exponents and logarithms in grade X at SMAN 4 Kota Jambi using STAD with Hands-On Mathematics. A true experimental design with a Pretest-Posttest Control Group involved three groups: experimental class I (STAD with Hands-On Mathematics), experimental class II (STAD), and a control class (Direct Instruction). Descriptive analysis showed an increase in average HOTS scores: 77.86 become 82.00 (class I), 73.67 become 75.33 (class II), and 68.11 become 71.56 (control). Normality and homogeneity tests confirmed assumptions were met. ANOVA indicated significant differences among groups (F = 10.233, p < 0.001). Post hoc Tukey tests revealed significant differences between class I and II (p = 0.016) and class I and control (p < 0.001), while class II and control showed no significant difference (p = 0.327). The study demonstrates that STAD with Hands-On Mathematics is effective in enhancing students’ HOTS in mathematics.